Niassa, Mozambique: The Makhuwa-Shirima and Yao Peoples - Center for the Study of Global Christianity (Gordon-Conwell Theological Seminary, 2020)
The region of modern-day Mozambique has always been strategic for global trade. Since at least the medieval period its coasts have been visited by traders from India, Somalia, Ethiopia, and beyond. Portuguese explorer Vasco da Gama arrived in 1498, marking the beginning of nearly 500 years of Portuguese colonial rule of the territory. Mozambique achieved independence from Portugal in 1975, but subsequently experienced a series of civil wars from 1977 to 1992. Democratic elections in 1994 resulted in a relatively stable modern republic. Despite the history of power struggles, Mozambique’s indigenous population, which include the Yao and the Makhuwa-Shirima peoples, carries with it a unique legacy challenged by colonialism and trade. To the present-day, these peoples maintain a presence in Mozambique; albeit, one that is continually threatened by cultural imperialism and globalization. The Yao (also, Wayao) people, many of whom live in Niassa province, largely rejected foreign colonial rule and the Christianity associated with it. Islam, introduced by Arab traders, was perceived a better cultural fit for the Yao and allowed for greater economic opportunities in light of the extant slave trade that ran through the Lake Niassa region and along the Rovuma River. As a result, the Yao were quite prosperous. Famous Scottish pioneer missionary-explorer David Livingstone passed through Niassa in search of the most direct route to the African interior. One of his most trusted African colleagues was a Yao man.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; society / sociedade